Нове тепломасообмінне обладнання для інтенсифікації процесу біологічного очищення стічних вод - Ободович, О. М.; Саблій, Л. А.; Сидоренко, В.В.; Коренчук, М.С. (Energy and Automation, 2017)
NEW HEAT AND MASS TRANSFER EQUIPMENT FOR INTENSIFICATION OF BIOLOGICAL WASTEWATER TREATMENT PROCESS О. Obodovych, L. Sabliy, V. Sydorenko, М. Korenchuk The wastewater treatment in poultry farms, pig farms and other livestock industry enterprises is compulsory. Lately biological methods of wastewater treatment are being used more and more widely. Biological methods are the most promising in economical and ecological sense. As a priority, considered combined methods with use of aerobic and anaerobic processes. For provide an oxidation of organic pollutants by microorganisms of activated sludge a forced aeration of wastewater and activated sludge mixture is used. A dissolution of poorly soluble gases (like oxygen) in water solutions more effective with use of mechanical systems of aeration (mixers etс.). At the same time, it should be noted that in such systems significant pressure differences and shear stresses can cause damage and destruction of microorganisms of activated sludge. Finding an optimal relationship between the intensity of the effect that causes the active mixing and dispersion of air bubbles in the medium and provision of conditions that are comfortable for microorganisms of activated sludge remains a priority task in the development of mechanical aeration systems. The purpose of the study is to evaluate prospects of application of equipment, that realize discrete-pulsed energy input method for intensification mass transfer and oxidation of organic pollutants by microorganisms of activated sludge. The experimental aeration-oxidation set-up of rotor type is a closed loop system consisting of collector-storage, aerator-oxidizer and recirculation pipe. The air for aeration of the mixture of water and activated sludge is self-suctioned through an air pipe with an ejecting head at the end to the air inlet pipe. The air-fed mixture obtained in the ejection zone enters an aerator-oxidizer, consisting of a rotor-pulsating unit and a rotary impeller of a centrifugal pump. The operating volume of the aerator-oxidizer is 0.0015 m3. An oxygen-saturated gas-air mixture through the recirculation pipeline returns to the collector-storage. In the course of the research, it was possible to vary both the structural parameters of the rotor-pulsating unit (the number and shape of the slots, between the gap between stator and rotor) and the hydrodynamic characteristics (liquid flow rate, gas flow rate, etc.). As an object of research, activated sludge from the primary clarifiers of the Bortnychi wastewater treatment plant and water from water supply was considered. As the main parameter the sludge index which is the ratio of the mass of the activated sludge to the volume it occupies was used. This parameter characterizes the ability of activated sludge to sedimentation in secondary clarifier and directly affects the purification time. Protozoa, which is part of the activated sludge, was determined visually, using a Karl Zeiss Axio Imager microscope. The obtained data testify that the use of the heat and mass transfer equipment of the rotor type for aeration in biological methods of wastewater treatment is possible taking into account the vulnerability of active sludge organisms to mechanical influences as a result of passing through the working elements of the aerator-oxidizer. It is determined that the state of activated sludge during treatment significantly depends on the design of the rotor-pulsating unit.